Clinical benefits of systemic amoxicillin/metronidazole may depend on periodontitis severity and patients' age: an exploratory sub-analysis of the ABPARO trial - Eickholz, Peter; Koch, Raphael; Kocher, Thomas; Hoffmann, Thomas; Kim, Ti-Sun; Meyle, Jörg; Kaner, Doğan; Schlagenhauf, Ulrich; Harmsen, Dag; Harks, Inga; Ehmke, Benjamin (Journal of clinical periodontology, 2019)
Aim The aim was to identify benefit thresholds for clinical variables. We hypothesize, if variables fall below or exceed these threshold levels, systemic amoxicillin/metronidazole may contribute to reducing progression of periodontitis. Material & Methods This is an explorative per-protocol collective analysis (n = 345) conducted on the placebo-controlled, multi-centre ABPARO trial (ClinicalTrials.gov NCT00707369). Patients received debridement with systemic amoxicillin 500 mg/metronidazole 400 mg (3×/day, 7 days, n = 170) or placebo (n = 175) and maintenance therapy every three months. To identify thresholds, each of the following baseline characteristics was classified into two groups (≥threshold value/<threshold value): bleeding on probing, extent of pocket probing depth (PPD) ≥ 5 mm, mean clinical attachment level and age. Treatment effect (% of sites with new attachment loss ≥ 1.3 mm at 27.5 months post-treatment) was calculated. Results Adjunctive antimicrobials reduced median new attachment loss in patients < 55 years (5.2%), or with ≥ 35% PPD ≥ 5 mm (4.5%) or with a mean attachment level > 5 mm (5.2%) at baseline compared to the placebo (9.0%, 11.6%, and 12.5%, respectively; p < 0.005). Conclusions The clinical benefits of systemic amoxicillin/metronidazole may depend on periodontitis severity and patients' age.
Gesehen am 18.11.2019